Indinization and Indian Traditional Practices for Modern Sports Performance (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: India has a rich cultural heritage of traditional sports, physical training methods, and values that have been practiced for centuries. Performance in sports depends not only on physical skills but also on discipline, attitude, regularity, mutual respect, and gratitude towards coaches, teachers, and even training equipment. These qualities are deeply rooted in Indian culture, as reflected in traditions such as Guru Vandana, Guru Poornima celebrations, Ayudha Pooja, and the Gurukul system of learning. Integrating such cultural values with indigenous training practices like yoga, mallakhamb, kalaripayattu, and pehlwani provides a holistic approach to modern sports training. This article examines the significance of Indian traditions in shaping athletic performance, the benefits of traditional practices in contemporary sports science, and the future prospects of indigenization in sports training.